Investigation of acetylcholinesterase and mammalian DNA topoisomerases, carbonic anhydrase inhibition profiles, and cytotoxic activity of novel bis(-aminoalkyl)phosphinic acid derivatives against human breast cancer - Dastan, Taner; Kocyigit, Umit M.; Dastan, Sevgi Durna; Kilickaya, Pakize Canturk; Taslimi, Parham; Cevik, Ozge; Cetin, Ahmet (Wiley, 2017)
The aim of this study was to evaluate biologically active novel molecules having potentials to be drugs by their antitumor properties and by activities of apoptotic caspase and topoisomerase. Following syntheses of novel eight bis(-aminoalkyl)phosphinic acid derivatives (4a-h) as a result of array of reactions, compounds were evaluated by cytotoxic effects in vitro on human breast cancer (MCF-7) and normal endothelial (HUVEC) cell lines. All phosphinic acid derivatives were effective for cytotoxicity on both MCF-7 and HUVEC lines, while 4c, 4e, and 4f compounds were found significantly more effective. For the evaluation of antitumor properties of compounds in a highly sensitive method, their effects on inhibiting topoisomerases I and II were investigated. Also, some of the bis(-aminoalkyl)phosphinic acid derivatives (4a, 4e-h) showed nice inhibitory action against acetylcholinesterase and human carbonic anhydrase isoforms I and II.
Keywords: acetylcholinesterase; cytotoxicity; carbonic anhydrase; phosphinic acid; topoisomerase